CONTEMPORARY MENTAL HEALTH ISSUES IN PAKISTAN: FOCUS ON FORENSIC PSYCHIATRY - Ahmed Mashood (Journal of Pakistan Psychiatric Society, 2025)
Mental health in Pakistan faces critical challenges, including cultural stigma, socioeconomic barriers, inadequate healthcare infrastructure, and the psychological toll of conflict. Widespread stigma fosters discrimination and silence, highlighting the need for awareness and education. Economic hardship and limited access to education further exacerbate mental health struggles, while an acute shortage of professionals and facilities hampers care. Youth face growing pressures from academics and social media, necessitating school-based counselling services. Prisons and forensic settings lack proper mental health support, endangering both inmates and public safety. To address these issues, policymakers must prioritise increased funding, widespread mental health screenings, community-based interventions, forensic services, and staff training in correctional facilities. Mobile units and rehabilitation programs should be integrated into public health strategies. This editorial emphasises the urgent need for comprehensive reforms to address the mental health crisis in Pakistan, focusing on systemic improvements and societal change.